Pengaruh Label Halal, Asosiasi Merek, Iklan, dan Celebrity Endroser terhadap Keputusan Pembelian (Survei Pada Konsumen Wardah Di Malang - Premi Wahyu Widyaningrum (UNIVERSITAS PGRI MADIUN, 2018)
ABSTRACTMoslem consumers tend to choose products that are declared halal compared with products that have not been declared halal by the authorities. No exception in terms of cosmetic purchase. Cosmetics is one such purchase that emphasizes emotional engagement, so sometimes idol figures (celebrities) who become brand ambassadors in a cosmetic ad can stimulate purchases. Halal Label Relationships with Advertisements, Celebrity Endrosers, Brand Associations, and Purchase Decisions are how marketers create halal and certified products so that Muslim consumers feel protected to consume them. The purpose of this study is to determine the factors that affect consumer purchasing decisions on Wardah cosmetic products. This type of research is explanatory with quantitative approach and survey method. The research location is in Malang Town Square with total sample of 57 respondents. The findings indicate that there is a positive and significant influence among the variables studied.Keyword: Halal Lable, Brand Asosiation, Ads, Celebrity Endroser, Purchase Decisions